2021
DOI: 10.1007/s00249-021-01568-8
|View full text |Cite
|
Sign up to set email alerts
|

Systems of conductive skin for power transfer in clinical applications

Abstract: The primary aim of this article is to review the clinical challenges related to the supply of power in implanted left ventricular assist devices (LVADs) by means of transcutaneous drivelines. In effect of that, we present the preventive measures and post-operative protocols that are regularly employed to address the leading problem of driveline infections. Due to the lack of reliable wireless solutions for power transfer in LVADs, the development of new driveline configurations remains at the forefront of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 138 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…The latter is an important technical and clinical challenge associated with foreign body reactions against biomaterials [129]. Thus, the development of novel material methods with the potential to reduce foreign body reactions [130][131][132][133] shall facilitate the acquisition of local pressure measurements, untainted by the contributions of adverse tissue reactions. Catheters with miniaturized transducers on their tip have also been used for the measurement of interstitial fluid pressure in tumors [134].…”
Section: Methods For the Measurement Of Hp In Vivomentioning
confidence: 99%
“…The latter is an important technical and clinical challenge associated with foreign body reactions against biomaterials [129]. Thus, the development of novel material methods with the potential to reduce foreign body reactions [130][131][132][133] shall facilitate the acquisition of local pressure measurements, untainted by the contributions of adverse tissue reactions. Catheters with miniaturized transducers on their tip have also been used for the measurement of interstitial fluid pressure in tumors [134].…”
Section: Methods For the Measurement Of Hp In Vivomentioning
confidence: 99%
“…Related to the extracorporeal energy delivery, INTERMACS reported that within 1 year of LVAD implantation, the most common infectious complications are pneumonia (23%), sepsis (20%), and driveline site infections (19%), often caused by skin flora [ 52 , 74 , 75 , 76 ]. In particular, biofilm formation at the interface of the driveline with the injured skin poses a challenge to eradicating bacterial pathogenesis [ 77 ]. According to the European Registry for Patients with Mechanical Circulatory Support, sepsis, along with multiple organ failure, is the leading cause of early mortality in LVAD patients [ 52 , 78 , 79 ].…”
Section: Complications Associated With Bridge To Transplant Lvad Therapymentioning
confidence: 99%
“…Anti-infective therapeutic protocols may include wound dressing in combination with adjunctive therapies such as vacuum-assisted closure therapy, cold atmospheric plasma, or antibiotic beads [ 77 ]. In many cases, however, the therapeutic benefits are negated by recurrent infections associated with biofilm persistence [ 77 ]. Alternatively, severe driveline infections can be treated with surgical intervention, such as driveline repositioning followed by wound debridement [ 77 ].…”
Section: Complications Associated With Bridge To Transplant Lvad Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, LVAD power demand is high, usually 5–30 W. This requires an external power source connected to the LVAD via a percutaneous driveline. The driveline frequently becomes infected, resulting in recurrent hospital admissions and complications including life-threatening sepsis, LVAD failure and premature death [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%